Non-stick packaging film
Through the combination of polymer microbeads and nano-microcrystalline wax, a food packaging film with superhydrophobic properties is constructed, which solves the problem of food packaging film adhesion and achieves a low-cost and efficient non-stick effect.
Patent Information
- Application Number
- CN202323624943.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2033-12-29
AI Technical Summary
The existing food packaging film is prone to adhere to food during use, resulting in inconvenience and waste. The existing preparation method for imitating lotus leaf surfaces is expensive and the prospect of industrialization is unclear.
Using a non-stick packaging film composed of polymer microbeads, adhesives and nanocrystalline wax, the micro-nano structure on the surface of the composite film is constructed through polymer microbeads, combined with silane-modified wax, reduces the surface tension, and forms superhydrophobic Performance membrane.
It realizes a low-cost production non-stick packaging film, with excellent superhydrophobic properties, contact angle greater than 170° and rolling angle less than 3°, significantly reducing adhesion risks and production costs.
Smart Images

Figure CN222331828U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to a preparation method of a new polymer film material, in particular to a non-stick packaging film. Background Art
[0002] Viscous liquid foods, such as ketchup, jam, and honey, have become a common sight on people's daily tables due to their fluid properties. However, consumers often face a problem during consumption, that is, food tends to adhere to the surface of the packaging material, which brings inconvenience to the eating experience and also leads to food waste. Therefore, it is necessary to develop a new food packaging film material that is non-sticky and still has good performance to overcome this problem.
[0003] The surface of some plant leaves in nature has super-hydrophobic properties and self-cleaning functions. The most typical example is the "lotus leaf self-cleaning effect" formed on the surface of lotus leaves. The super-hydrophobic property of the lotus leaf surface is the result of the combined effect of its microstructure and surface chemical composition. This special surface property allows water droplets to roll on the surface of the lotus leaf and slide off quickly, while taking away pollutants on the surface, thus keeping the lotus leaf clean.
[0004] The superhydrophobicity of the lotus leaf surface is mainly caused by two factors: microstructure and surface chemical composition.
[0005] Microstructure: The surface of the lotus leaf has a microscopic multi-level structure, which is often described as a "wax paper" structure. This structure is composed of tiny soft micro-hairs, which form tiny gaps between these micro-hairs. These microstructures reduce the area of contact between the surface and the water, so that the water droplets are almost not in direct contact with the surface, but suspended between the micro-hairs. This special structure reduces the effect of surface tension on the water droplets, making it easier for the water droplets to roll and quickly leave the surface.
[0006] Surface chemical composition: The surface of lotus leaves is covered with a layer of waxy substances. This waxy substance makes the surface of lotus leaves hydrophobic, and water droplets cannot expand on the surface, but exist in a nearly spherical shape. This surface chemical composition further reduces the adhesion between water and the surface of lotus leaves, which helps water droplets slide quickly on the surface.
[0007] The method of preparing lotus leaf-like surface mainly involves two aspects: preparation of microstructure and coating of surface chemical components. The common preparation technology of lotus leaf-like surface can be divided into preparation of microstructure, coating of surface chemical components and self-assembly technology. At present, many methods have been used to prepare lotus leaf-like surface. Including etching method, phase separation and self-assembly method, hydrothermal method, chemical deposition and electrodeposition method, sol-gel method, electrospinning method, carbon nanotube method, template method and other methods. Although there are many methods for preparing super-hydrophobic surface, the above methods are costly, have great limitations, and the prospects for industrialization are unclear. Utility Model Content
[0008] The utility model aims at solving various deficiencies in the prior art and provides a non-stick packaging film.
[0009] In order to achieve the above-mentioned purpose, the utility model is realized through the following technical solutions:
[0010] The utility model discloses a non-stick packaging film, which comprises from bottom to top a substrate layer, an adhesive layer containing polymer micro beads and a nano-microcrystalline wax layer.
[0011] As a further improvement, the polymer microbeads described in the utility model are any one of polystyrene microbeads, polyethylene microbeads, polypropylene microbeads and polylactic acid microbeads, and the particle size thereof is 5-50 μm.
[0012] As a further improvement, the polymer microbeads described in the utility model are polystyrene microbeads with a particle size of 10-30 μm.
[0013] As a further improvement, the adhesive layer containing polymer microbeads described in the utility model is an adhesive containing polymer microbeads, the adhesive wraps the polymer microbeads, and the weight ratio of the adhesive to the polymer microbeads is 1:0.1-1.0.
[0014] As a further improvement, the nano-microcrystalline wax layer described in the utility model is a solidified modified wax.
[0015] As a further improvement, the modified wax described in the utility model is silane-modified polyethylene wax or silane-modified polypropylene wax.
[0016] As a further improvement, the modified wax of the utility model is applied in an amount of 0.1-20 g / m 2 .
[0017] As a further improvement, in a hydrophobicity test, the surface of the non-stick packaging film prepared in the utility model has a contact angle greater than 160° and a rolling angle less than 5°.
[0018] The beneficial effects of the utility model are as follows:
[0019] 1. The utility model provides a non-stick packaging film, which uses polymer microbeads to construct a micro-nano structure on the surface of the composite film. The cost of polymer microbeads is extremely low, especially polystyrene microbeads, so the utility model has excellent cost advantages. In addition, the density of the polymer microbeads is basically the same as the density of the adhesive, especially the polystyrene microbeads have a natural similar miscibility with the conventional adhesive system, and can not cause impact on the existing coating equipment during the mixed coating process, greatly reducing the coating production cost. Third, after heating, the polymer microbeads also have good hot melt bonding properties, which is greatly beneficial to the subsequent heat sealing packaging method of the composite film, further reducing production costs. Fourth, the polymer microbeads have uniform particle size and are extremely easy to be evenly dispersed on the surface of the substrate layer to form a uniform and controllable micro-nano structure, which effectively improves the super-hydrophobic performance of the non-stick packaging film. Fifth, the spherical structure and smooth surface of the polymer microbeads can greatly reduce the contact area between the composite film and the viscous substance, further improving the super-hydrophobic performance of the non-stick packaging film.
[0020] 2. In the utility model, a rough surface structure with a micro-nano structure is prepared by using polymer microbeads and adhesives, and silane-modified polyethylene wax or silane-modified polypropylene wax is further used to further modify the rough surface to reduce the surface tension. Silane-modified polyethylene wax or silane-modified polypropylene wax significantly reduces the surface tension of polyethylene wax or polypropylene wax through silane modification, improves hydrophobicity, and improves mechanical strength. The ultra-low surface energy of silane-modified wax combined with the rough surface structure with a micro-nano structure obtains a non-stick packaging film with excellent super-hydrophobic properties.
[0021] 3. The utility model has low cost and obtains a non-stick packaging film with excellent super hydrophobic performance. In the hydrophobicity experiment, the contact angle is greater than 170° and the rolling angle is less than 3°. The general definition of super hydrophobic is that the contact angle is greater than 150° and the rolling angle is less than 10°. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a structural schematic diagram of a non-stick packaging film;
[0023] In the figure, 1 is a substrate layer, 2 is polymer microbeads, 3 is an adhesive layer containing polymer microbeads, and 4 is a nano-microcrystalline wax layer. DETAILED DESCRIPTION
[0024] The utility model discloses a non-stick packaging film, which includes from bottom to top a substrate layer 1, an adhesive layer 3 containing polymer microbeads, and a nano-microcrystalline wax layer 4. The polymer microbeads 2 are any one of polystyrene microbeads, polyethylene microbeads, polypropylene microbeads, and polylactic acid microbeads, and the particle size thereof is 5-50 μm. Preferably, the polymer microbeads 2 are polystyrene microbeads, and the particle size is 10-30 μm. The adhesive layer 3 containing polymer microbeads is an adhesive containing polymer microbeads 2, the adhesive wraps the polymer microbeads 2, and the weight ratio of the adhesive to the polymer microbeads 2 is 1:0.1-1.0. The nano-microcrystalline wax layer 4 is a solidified modified wax, and the modified wax is silane-modified polyethylene wax or silane-modified polypropylene wax, and the application quantity of the modified wax is 0.1-20 g / m 2 In the hydrophobicity test, the contact angle of the non-stick packaging film surface is greater than 160° and the rolling angle is less than 5°. The preparation method of the utility model is as follows:
[0025] 1) fully mixing the adhesive layer raw material and the polymer microbeads 2 to form an adhesive layer containing the polymer microbeads 2, adjusting the appropriate viscosity of the adhesive layer containing the polymer microbeads 2 with a solvent, coating it on the surface of the substrate layer 1, and obtaining the adhesive layer 3 containing the polymer microbeads after drying;
[0026] 2) Subsequently, the modified wax solution is sprayed onto the obtained adhesive layer 3 containing polymer microbeads through a nozzle, and a nano-microcrystalline structure is formed during the curing process, namely, a nano-microcrystalline wax layer 4. Finally, a composite film structure having a nano-microcrystalline wax layer 4 is obtained, namely, a non-stick packaging film.
[0027] The technical solution of the present utility model is further described in detail below in conjunction with specific embodiments, but the scope of the present utility model is not limited to the embodiments.
[0028] Example 1
[0029] 1) A vapor-deposited polyethylene terephthalate film (VMPET) is used as the substrate, and a coating process is performed on the PET surface to form a substrate layer 1.
[0030] 2) The raw material of the adhesive layer is a heat sealant polyurethane TPU resin adhesive. A certain amount of ethyl acetate is added to dissolve, and a certain amount of polystyrene microbeads are added, and the coating is obtained after sufficient mixing. Among them, the particle size of the polystyrene microbeads is 5μm. The weight ratio of the adhesive layer raw material and the polystyrene microbeads is 1:0.1. The viscosity of the obtained coating is adjusted to 1000cps, and then the obtained coating is applied on the surface of the substrate by a roller coating method, and dried at 180°C for 30s to obtain a fine structure. After drying, an adhesive layer 3 containing polymer microbeads is obtained.
[0031] 3) Subsequently, the silane-modified polyethylene wax liquid is sprayed onto the obtained adhesive layer 3 containing polymer microbeads through a nozzle, and a nano-microcrystalline structure is formed during the curing process to form a nano-microcrystalline wax layer 4, and finally a composite film structure having a nano-microcrystalline wax layer 4 is obtained. The application amount of the modified wax is 0.1 g / m 2 .
[0032] 4) In the hydrophobicity experiment, the contact angle of the surface of the prepared non-stick packaging film was 161° and the rolling angle was 5°.
[0033] Example 2
[0034] 1) A polyethylene film (LDPE) is used as the substrate, and a coating treatment is performed on the surface thereof to form a substrate layer 1.
[0035] 2) The raw material of the adhesive layer is an acrylic resin adhesive product. A certain amount of ethyl acetate is added to dissolve, and a certain amount of polyethylene microbeads are added, and the coating is obtained after sufficient mixing. Among them, the particle size of the polyethylene microbeads is 50 μm. The weight ratio of the adhesive layer raw material and the polyethylene microbeads is 1:1.0. The viscosity of the obtained coating is adjusted to 1000 cps, and then the obtained coating is applied on the surface of the substrate by a roller coating method. After drying, an adhesive layer 3 containing polymer microbeads is obtained.
[0036] 3) Subsequently, the silane-modified polypropylene wax liquid is sprayed onto the obtained adhesive layer 3 containing polymer microbeads through a nozzle, and a nano-microcrystalline structure is formed during the curing process to form a nano-microcrystalline wax layer 4, and finally a composite film structure having a nano-microcrystalline wax layer 4 is obtained. The application amount of the modified wax is 20 g / m 2 .
[0037] 4) In the hydrophobicity experiment, the contact angle of the prepared non-stick packaging film surface was 163° and the rolling angle was 5°.
[0038] Example 3
[0039] 1) A vapor-deposited polyethylene terephthalate film (VMPET) is used as the substrate, and a coating process is performed on the PET surface to form a substrate layer 1.
[0040] 2) The raw material of the adhesive layer is a heat sealant polyurethane TPU resin adhesive. A certain amount of ethyl acetate is added to dissolve, and a certain amount of polypropylene microbeads are added, and the coating is obtained after sufficient mixing. Among them, the particle size of the polypropylene microbeads is 10μm. The weight ratio of the adhesive layer raw material and the polystyrene microbeads is 1:0.2. The viscosity of the obtained coating is adjusted to 1000cps, and then the obtained coating is applied on the surface of the substrate by a roller coating method, and dried at 180°C for 30s to obtain a fine structure. After drying, an adhesive layer 3 containing polymer microbeads is obtained.
[0041] 3) Subsequently, a n-hexane solution of silane-modified polyethylene wax (5% mass concentration) is sprayed onto the obtained adhesive layer 3 containing polymer microbeads through a nozzle, and a nano-microcrystalline structure is formed during the curing process to form a nano-microcrystalline wax layer 4, and finally a composite film structure having a nano-microcrystalline wax layer 4 is obtained. The application amount of the modified wax is 1.0 g / m 2 .
[0042] 4) In the hydrophobicity experiment, the contact angle of the prepared non-stick packaging film surface was 167° and the rolling angle was 4°.
[0043] Example 4
[0044] 1) A vapor-deposited polyethylene terephthalate film (VMPET) is used as the substrate, and a coating process is performed on the PET surface to form a substrate layer 1.
[0045] 2) The raw material of the adhesive layer is a heat sealant polyurethane TPU resin adhesive. A certain amount of ethyl acetate is added to dissolve, and a certain amount of polylactic acid microbeads are added, and the coating is obtained after sufficient mixing. Among them, the particle size of the polylactic acid microbeads is 30μm. The weight ratio of the adhesive layer raw material and the polystyrene microbeads is 1:0.5. The viscosity of the obtained coating is adjusted to 1000cps, and then the obtained coating is applied on the surface of the substrate by a roller coating method, and dried at 180°C for 30s to obtain a fine structure. After drying, an adhesive layer 3 containing polymer microbeads is obtained.
[0046] 3) Subsequently, the wax liquid of silane-modified polyethylene wax is sprayed on the obtained adhesive layer 3 containing polymer microbeads through a nozzle, and a nano-microcrystalline structure is formed during the curing process to form a nano-microcrystalline wax layer 4, and finally a composite film structure having a nano-microcrystalline wax layer 4 is obtained. The application amount of the modified wax is 10 g / m 2 .
[0047] 4) In the hydrophobicity experiment, the contact angle of the prepared non-stick packaging film surface was 168° and the rolling angle was 4°.
[0048] Example 5
[0049] 1) A vapor-deposited polyethylene terephthalate film (VMPET) is used as the substrate, and a coating process is performed on the PET surface to form a substrate layer 1.
[0050] 2) The raw material of the adhesive layer is a heat sealant polyurethane TPU resin adhesive. A certain amount of ethyl acetate is added to dissolve, and a certain amount of polystyrene microbeads are added, and the coating is obtained after sufficient mixing. Among them, the particle size of the polystyrene microbeads is 20 μm. The weight ratio of the adhesive layer raw material and the polystyrene microbeads is 1:0.3. The viscosity of the obtained coating is adjusted to 1000 cps, and then the obtained coating is applied on the surface of the substrate by a roller coating method, and dried at 180°C for 30 seconds to obtain a fine structure. After drying, an adhesive layer 3 containing polymer microbeads is obtained.
[0051] 3) Subsequently, a n-hexane solution of silane-modified polyethylene wax (5% mass concentration) is sprayed onto the obtained adhesive layer 3 containing polymer microbeads through a nozzle, and a nano-microcrystalline structure is formed during the curing process to form a nano-microcrystalline wax layer 4, and finally a composite film structure having a nano-microcrystalline wax layer 4 is obtained. The application amount of the modified wax is 3 g / m 2 .
[0052] 4) In the hydrophobicity experiment, the contact angle of the prepared non-stick packaging film surface was 171° and the rolling angle was 3°.
[0053] Comparative Example 1
[0054] 1) The substrate is a vapor deposited polyethylene terephthalate film (VMPET), and a coating process is performed on the PET surface.
[0055] 2) The raw material of the adhesive layer is a heat sealant polyurethane TPU resin adhesive. A certain amount of ethyl acetate is added to dissolve, and a certain amount of polystyrene microbeads are added, and the coating is obtained after sufficient mixing. Among them, the particle size of the polystyrene microbeads is 20 μm. The weight ratio of the adhesive layer raw material and the polystyrene microbeads is 1:0.3. The viscosity of the obtained coating is adjusted to 1000 cps, and then the obtained coating is applied on the surface of the substrate by a roller coating method, and dried at 180°C for 30 seconds to obtain a fine structure. After drying, an adhesive layer 3 containing polymer microbeads is obtained.
[0056] 3) Without spraying the modified wax, the surface of the non-stick packaging film prepared had a contact angle of 131° and a rolling angle of 23° in the hydrophobicity experiment.
[0057] This shows that the micro-nanostructure composed only of polystyrene microbeads cannot achieve a superhydrophobic effect.
[0058] Comparative Example 2
[0059] 1) The substrate is a vapor deposited polyethylene terephthalate film (VMPET), and a coating process is performed on the PET surface.
[0060] 2) The adhesive layer raw material uses heat sealant polyurethane TPU resin adhesive. A certain amount of ethyl acetate is added to dissolve, and the obtained coating is adjusted to have a viscosity of 1000 cps. The obtained coating is then coated on the surface of the substrate by a roller coating method, and dried at 180° C. for 30 seconds to obtain an adhesive layer after drying.
[0061] 3) Subsequently, a n-hexane solution of silane-modified polyethylene wax (5% mass concentration) is sprayed on the obtained adhesive layer through a nozzle, and a composite film structure is obtained after curing. The application amount of the modified wax is 3 g / m 2 .
[0062] 4) In the hydrophobicity experiment, the contact angle of the prepared packaging film surface was 147° and the rolling angle was 15°.
[0063] This shows that without the micro-nanostructure constructed by polystyrene microbeads, the superhydrophobic effect cannot be achieved by modifying the wax surface alone.
[0064] Comparative Example 3
[0065] 1) The substrate is a vapor deposited polyethylene terephthalate film (VMPET), and a coating process is performed on the PET surface.
[0066] 2) The raw material of the adhesive layer is a heat sealant polyurethane TPU resin adhesive. A certain amount of ethyl acetate is added to dissolve, and a certain amount of polystyrene microbeads are added, and the coating is obtained after sufficient mixing. Among them, the particle size of the polystyrene microbeads is 20 μm. The weight ratio of the adhesive layer raw material and the polystyrene microbeads is 1:0.3. The viscosity of the obtained coating is adjusted to 1000 cps, and then the obtained coating is applied on the surface of the substrate by a roller coating method, and dried at 180°C for 30 seconds to obtain a fine structure. After drying, an adhesive layer 3 containing polymer microbeads is obtained.
[0067] 3) Subsequently, a polyethylene wax liquid is sprayed onto the obtained adhesive layer 3 containing polymer microbeads through a nozzle, and a composite film structure is obtained after curing. The polyethylene wax is applied in an amount of 5 g / m 2 .
[0068] 4) In the hydrophobicity experiment, the contact angle of the prepared packaging film surface was 150° and the rolling angle was 10°.
[0069] This shows that the surface energy of polyethylene wax is still relatively high, and the superhydrophobic effect of the composite film can be further effectively improved by modifying polyethylene wax with silane.
[0070] Finally, it should be noted that the above examples are only specific implementation examples of the present invention. Obviously, the present invention is not limited to the above examples, and there are many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.
Claims
1. A non-stick packaging film, characterized in that: The non-stick packaging film comprises from bottom to top a substrate layer, an adhesive layer containing polymer microbeads and a nano-microcrystalline wax layer, wherein the polymer microbeads are any one of polystyrene microbeads, polyethylene microbeads, polypropylene microbeads and polylactic acid microbeads, and the particle size thereof is 5-50 μm, the adhesive layer containing polymer microbeads is an adhesive containing polymer microbeads, the adhesive wraps the polymer microbeads, the weight ratio of the adhesive to the polymer microbeads is 1:0.1-1.0, and the wax in the nano-microcrystalline wax layer is applied in an amount of 0.1-20 g / m 2 .
2. The non-stick packaging film according to claim 1, characterized in that: The polymer microbeads are polystyrene microbeads with a particle size of 10-30 μm.
3. The non-stick packaging film according to claim 1, characterized in that: The nano-microcrystalline wax layer is solidified modified wax.
4. The non-stick packaging film according to claim 3, characterized in that: The modified wax is silane-modified polyethylene wax or silane-modified polypropylene wax.
5. The non-stick packaging film according to claim 1, 2, 3 or 4, characterized in that: In a hydrophobicity experiment, the surface of the prepared non-stick packaging film has a contact angle greater than 160° and a rolling angle less than 5°.